COTIP: Cotton TILLING Platform, a Resource for Plant Improvement and Reverse Genetic Studies - Aslam, Usman; Cheema, Hafiza M. N.; Ahmad, Sheraz; Khan, Iqrar A.; Malik, Waqas; Khan, Asif A. (Frontiers in Plant Science, 2016)
Cotton is cultivated worldwide for its white fiber, of which around 90 % is tetraploid upland cotton (Gossypium hirsutum, L.) carrying both A and D genome. Since centuries, yield increasing efforts for the cotton crop by conventional breeding approaches have caused an extensive erosion of natural genetic variability. Mutation based improvement strategies provide an effective way of creating new allelic variations. Targeting Induced Local Lesions IN Genomes (TILLING) provides a mutation based reverse genetic strategy to create and evaluate induced genetic variability at DNA level. Here we report development and testing of TILLING populations of allotetraploid cotton (G. hirsutum) for functional genomic studies and mutation based enrichment of cotton genetic resources. Seed of two cotton cultivars “PB-899 and PB-900” were mutagenized with 0.3 % and 0.2% (v/v) EMS respectively. The phenotyping of M1 and M2 populations presented numerous mutants regarding the branching pattern, leaf morphology, disease resistance, photosynthetic lesions and flower sterility. Molecular screening for point mutations was performed by TILLING PCR aided CEL1 mismatch cleavage. To estimate the mutation frequency in the mutant genomes, five gene classes were TILLed in 8000 M2 plants of each var. “PB-899” and “PB-900”. These include actin (GhACT), Pectin Methyl Esterase (GhPME), sucrose synthase (GhSUS), resistance gene analogue (RGA) and defense response gene (DRGs). The var. PB-899 was harboring 47 % higher mutation induction rate than PB-900. The highest rate of mutation frequency was identified for NAC-TF5 (EU706348) of DRGs class, ranging from 1/58kb in PB-899 to 1/105 kb in PB-900. The mutation screening assay revealed the presence of significant proportion of induced mutations in cotton TILLING populations such as 1/153kb and 1/326kb in var. “PB-899” and “PB-900” respectively. The establishment of a cotton TILLING platform (COTIP) and data obtained from the resource TILLING population suggest its effectiveness in widening the genetic bases of cotton for improvement and utilizing it for subsequent reverse genetic studies of various genes.